Developing business skills with an Agribusiness Innovation Hub [Ghana] - Nganwani Tia, Moses (Technical Centre for Agricultural and Rural Cooperation, 2018)
To support the development of viable agribusiness ventures in Ghana, an agribusiness Innovation Hub has worked with over 1,500 youths to provide them with business skills and training. The initiative is also helping entrepreneurs to pilot their ideas across the country, and providing much needed investment to enable the entrepreneurs to scale-out their businesses successfully.